The validity and reliability of psychometric profile for depression, anxiety and stress scale (DASS21) instrument among Malaysian undergraduate students - Ahmad, Noorlila; Roslan, Samsilah; Othman, Shamsudin; Abdul Shukor, Shureen Faris; Abu Bakar, Abu Yazid (Human Resource Management Academic Research Society, 2018)
This study aims to investigate the psychometric attributes of DASS21 instrument of depression, anxiety, and stress among Malaysian university undergraduate students, where negative emotional disturbance is evaluated in the respect of frequency and severity. During this study, English and Malay were the languages used for the descriptive investigation on the severity of emotional disturbance and psychometrics analysis. Across-sectional study was conducted among (N = 390) undergraduate students from Universiti Putra Malaysia, through a simple random exercise. This was followed by collection of data on the final respondents through AMOS for confirmatory factor analysis (CFA) and measurement. An excellent structure of the 21-items in three DASS21 sub-constructs was displayed, with 18 out of 21 items were produced from adequate construct validity. It exhibited a positive factor loading, which amounted to 0.5 and higher. In terms of internal consistency, the alpha values for anxiety (α=0.850), stress (α=0.859), and depression (α=0.910) were shown. A positive consistency of Cronbach’s Alpha (α=0.926) could also be seen from the overall score where all items were included. Thus, DASS21 can be utilized as a measurement tool to identify the health condition of students with negative emotional disturbances.